Omega-3 fatty acids and mortality in patients referred for coronary angiography: the Ludwigshafen Risk and Cardiovascular Health Study - Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; März, Winfried (Atherosclerosis, 2016)
Background and aims: There is an ongoing debate whether omega-3-fatty acids protect from cardiovascular disease mortality. We examined the associations of erythrocyte omega-3 fatty acids with mortality in patients referred for coronary angiography. Methods: Erythrocyte omega-3 fatty acid proportions were measured at baseline in 3259 participants of the Ludwigshafen Risk and Cardiovascular Health Study (LURIC) using the HS-Omega-3 Index method. Associations of omega-3 fatty acid proportions with mortality were investigated using Cox proportional hazards regression. Results: During a median follow-up of 9.9 years, 975 patients (29.9%) died, 614 patients (18.8%) from cardiovascular causes. Proportions of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were inversely associated with all-cause and cardiovascular mortality in models adjusted for conventional cardiovascular risk factors. The strongest association was observed for EPA with a hazard ratio (HR) of 0.89 (0.83-0.96) per increase of one standard deviation. Furthermore, we obtained evidence for a non-linear relation between EPA and mortality. Conclusions: EPA and DHA were associated with reduced mortality in LURIC, independent of other risk factors, with the association of EPA with mortality being non-linear.
Gesehen am 25.02.2019
Available online 1 July 2016